Cultural Intelligence in Military Leaders and Its Influence on Performance through Cultural Intelligence Scale - Setyawan, Imanda; Hadna, Agus Heruanto; Kutanegara, Pande Made; Darwin, Muhadjir (Interdisciplinary Social Studies, 2023)
Background: The existence of strong ethnic factors in Nusa Tenggara Timur (NTT) and the diversity of dioceses is the basis that cultural intelligence needs to be applied by all soldiers so they can carry out their duties and to be accepted by society. Aim: This paper aims to determine the cultural intelligence of leaders and explain the urgency of the performance in military organization based on a number of cases in NTT involving the role of the military leadership in solving problems Method: Using a mixed method with a quantitative descriptive approach which was tested on military leaders at Military Resort Command 161 NTT, the data shows that the cultural intelligence measured using the Cultural Intelligence Scale (CQS) is dominated by moderate leaders. Findings: In addition, based on the results of statistical tests through correlation-regression tests, it shows that cultural intelligence has a significant effect on leader performance. This shows how urgent cultural intelligence is for soldiers, especially in carrying out their performance directly related to the community. Internal organizational factors that significantly affect the cultural intelligence of leaders are expected to be a reference in making policies or programs that can increase the cultural intelligence of military personnel.